CONSTRUCTION ACCOUNTABILITY IN THE RENTAL HOUSE SERVICE BUSINESS - Kustiwi, Irda Agustin; Hwihanus, Hwihanus (JEA17: Jurnal Ekonomi Akuntansi, 2022)
This study aims to uncover the construction of accountability owned by rental house service business owners domiciled in Surabaya. The approach used the phenomenological paradigm to dig deeper into the value of ever-changing and dynamic phenomena. The results of the study explained that homeowners in running their business are not only profit-oriented which is used as the initial intention in running their business. Instead, it interprets the value of accountability more deeply, namely accountability which is in line with the original intention in doing business with high spirituality. The meaning of accountability is believed to consist of accountability for the tenants of the house, accountability for the environment around the rental house service business, and accountability to God as a reflection of the end of life. Limitations were found from the results of research that focused on rental business owners. So it is hoped that further research can dig deeper into the meaning of accountability that can be practiced by business people in various business fields by prioritizing accounting practices based on the value of local wisdom, culture, social, and religion.